One step closer to a licensed drug for AK.
Acanthamoeba keratitis (AK) is a relatively unknown disease affecting less than 0.1 in 10 000 EU citizens. Yet evidence suggests that its incidence is increasing. Whilst the market is too small for pharmaceutical companies, an EU-funded consortium has successfully conducted a Phase I clinical trial on PHMB as a treatment for AK, potentially preventing permanent visual impairment or blindness in patients.